2017
DOI: 10.1002/tesj.357
|View full text |Cite
|
Sign up to set email alerts
|

The impact of interface on ESL reading comprehension and strategy use: A comparison of e‐books and paper texts

Abstract: The use of e‐books in postsecondary education is projected to increase, yet many English as a second language (ESL) institutions have not yet incorporated e‐books into their curricula, in part due to a dearth of research regarding their potential impacts on ESL reading comprehension and strategy use. This study fills a gap in the existing research by investigating the impacts of contemporary e‐books on ESL strategy use and reading comprehension, in comparison to paper texts. Twenty‐two high‐intermediate ESL pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Consequently, different cognitive explanations have been put forward for the inferiority of digital text comprehension. For example, some authors suggested that the light emitted by digital media might contribute to visual fatigue and, consequently, increases cognitive load ( Benedetto et al, 2013 ), while others emphasized inferior learning strategies that people adopt on digital devices, thus, resulting in higher reading speed but shallower processing of the reading material (e.g., Isaacson, 2017 ; Morineau et al, 2005 ; Singer et al, 2019 ). Alternatively, it has also been suggested that people are more overconfident about their performance when reading on a computer that might lead to poorer test results ( Ackerman & Goldsmith, 2011 ).…”
Section: Characteristics Of Remote Testingmentioning
confidence: 99%
“…Consequently, different cognitive explanations have been put forward for the inferiority of digital text comprehension. For example, some authors suggested that the light emitted by digital media might contribute to visual fatigue and, consequently, increases cognitive load ( Benedetto et al, 2013 ), while others emphasized inferior learning strategies that people adopt on digital devices, thus, resulting in higher reading speed but shallower processing of the reading material (e.g., Isaacson, 2017 ; Morineau et al, 2005 ; Singer et al, 2019 ). Alternatively, it has also been suggested that people are more overconfident about their performance when reading on a computer that might lead to poorer test results ( Ackerman & Goldsmith, 2011 ).…”
Section: Characteristics Of Remote Testingmentioning
confidence: 99%
“…Some studies investigated the implementation of e-books to various levels of students, from young learners to adult learners, to support their learning experience. The studies implementing the ebook in English learning were mostly conducted experimentally ( Hsieh & Huang, 2020;Isaacson, 2017;Liu, Liu, & Chen, 2019;Wood et al, 2018;Yow & Priyashri, 2019). The other studies were survey study (Nie, Armellini, Witthaus, & Barklamb, 2011;Rogerson-Revell, Nie, & Armellini, 2012) and research and development (Hussain & Al Saadi, 2019;Wu, 2016).…”
Section: E-book In English Language Teachingmentioning
confidence: 99%
“…In the EFL environment, the reading comprehension between print and e-books are a major concern, as some ambivalent results on reading comprehension were found (Reich et al, 2016). Past studies cannot conclude whether e-book use was positive, negative, or neutral to the second language reading experience (Isaacson, 2017).…”
Section: Adoption Of Print Versus E-textbooks As a Teaching Practicementioning
confidence: 99%